2021
DOI: 10.1007/s10826-021-02122-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Perceived Family Involvement and Perceived Family Control during Emerging Adulthood: A Cross-Country Comparison in Southern Europe

Abstract: The aim of the present study was to explore gender differences in perceived parental involvement and perceived psychological and behavioral control during emerging adulthood in two Southern European countries (Spain and Portugal). Data were collected from 491 Portuguese and 552 Spanish undergraduate emerging adults (53.7 % women and 46.3 % men) aged between 18 and 29 years (M = 20.24 and SD = 2.12). Results indicated that women perceived higher levels of parental involvement than men in both countries, and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…As displayed in Table 2, among the five types, data analysis indicates that the mean difference between both groups is insignificant, meaning they almost have a similar perception of the importance of all the types. Research by García-Mendoza et al [67] added more perspective to the difference between both groups on parental involvement in which the perceived parental involvement scores of the female are more spread out than males. Meanwhile, the current finding suggested commonality of perception between male and female students differs from previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…As displayed in Table 2, among the five types, data analysis indicates that the mean difference between both groups is insignificant, meaning they almost have a similar perception of the importance of all the types. Research by García-Mendoza et al [67] added more perspective to the difference between both groups on parental involvement in which the perceived parental involvement scores of the female are more spread out than males. Meanwhile, the current finding suggested commonality of perception between male and female students differs from previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Italian youth tend to prolong academic study, delay entry into the labour market, live at home for a protracted period, and move out of their family homes predominantly for marriage and parenthood [ 49 ]. Family ties also tend to be very strong in Italy and other Mediterranean countries [ 50 , 51 ]. It is possible that these youth and family cultural factors may intensify the caregiving experience of young adults who care for a seriously ill family member.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated young adult caregiving is a significant public health issue given the global rise in the number of young adults caring for an ill or disabled family member [ 51 ], the often-hidden nature of youth caregiving, the vulnerability of emerging adults navigating critical development milestones, and the association between youth caregiving and greater risks for mental health problems. Results from the present study show that, during the COVID-19 pandemic, caregiving responsibilities remain elevated in young adult carers relative to non-carer peers and confirm the link between higher levels of caregiving responsibilities and poorer mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Then, considering only the dimensions showing a significant total effect, a path analysis approach was adopted to implement a parallel mediation model, hypothesizing that: (a) childhood trauma subdimensions would be significantly and positively related to love addiction (H 1 ); (b) childhood trauma subdimensions would be significantly and positively associated with unbalanced family functioning patterns (H 2 ); (c) unbalanced family functioning patterns would be significantly and positively related to love addiction (H 3 ); and (d) unbalanced family functioning patterns would significantly mediate the relationship between childhood trauma and love addiction (H 4 ). Finally, since previous research has shown the influence of gender in the perception of the family context (e.g., García-Mendoza et al, 2022), the role of gender as a covariate was explored in the model.…”
Section: Childhood Trauma and Love Addictionmentioning
confidence: 99%